Legume identity shapes soil multifunctionality and microbial networks in long-term cereal-based rotations - Shuting Yu; Shuo Li; Jin Yang; Kees Jan van Groenigen; Guiying Jiang; Mengru Wang; Beibei Wang; Fang Liu; Haitao Liu; Xiaolei Jie; Shiliang Liu (Applied Soil Ecology, 2026)

An in-situ measurement and assessment of evaporative cooling effects of low impact development facilities in a subtropical city - Chunhua Yan; Junjie Ding; Bei Wang; Longjun Qin; Zhe Shi; Guo Yu Qiu (Agricultural and Forest Meteorology, 2023)

Strategies to enhance tilapia immunity to improve their health in aquaculture - Bei Wang; Kim D. Thompson; Eakapol Wangkahart; Jidapa Yamkasem; Melba G. Bondad‐Reantaso; Puntanat Tattiyapong; Jichan Jian; Win Surachetpong (Reviews in Aquaculture, 2023)
Various emerging and re‐emerging diseases, such as streptococcosis, tilapia lake virus disease and infectious spleen and kidney necrosis virus disease, have had a significant economic impact on the tilapia industry over the last decade. These diseases have resulted in high levels of morbidity and mortality, production losses and trade restrictions. In the absence of effective husbandry management, disease prevention strategies and appropriate biosecurity measures, infectious diseases will continue to challenge the sustainability of global tilapia aquaculture. Strategies used to reduce the impact of disease include feeding probiotic and prebiotic supplements to enhance tilapia health and to modulate the fish's gut microbiota to improve gut health. Herbal medicines and immunostimulants are also used to enhance immunity to disease, while vaccines are available, or are under development, for a number of economically important pathogens affecting tilapia culture. This review provides an overview of the benefits of enhancing the immune response of tilapia to improve their health, and in turn reduce the levels of pathogens within tilapia farming systems.